Hubungan Tingkat Pengetahuan dengan Sikap Pencegahan terhadap HIV/AIDS pada Siswa-Siswi SMAN X - Anggi Sri Mulyani Rukmana; Ieva Baniasih Akbar (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Introduction: Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells, resulting in a decrease in the immune system. According to data from the World Health Organization (WHO) in 2019, it was stated that 38 million people were infected with HIV worldwide. According to the West Java Health Office in 2018, Cianjur City was ranked 13th out of 27 districts/cities with 124 cases reported. The spread of HIV is common among adolescents due to the low level of knowledge of HIV risk factors. Misunderstanding of knowledge about HIV/AIDS will make many youths experience confusion and tend to be influenced by untrue information. This can be exacerbated by the absence of supporting facilities at the level of formal education and the influence of information technology from unfiltered media. This study aims to determine the relationship between the level of knowledge and the attitude of prevention towards HIV/AIDS in the students of SMAN 1 Cianjur in the academic year 2020-2021. This type of research is quantitative with analytical observational method with cross sectional approach. Data were obtained from distributing questionnaires to students of SMAN 1 Cianjur totaling 95 samples. Data analysis using gamma test. Data processing was carried out using SPSS 2.0 application with a significance degree of p<0.005. The results showed that the level of knowledge was lacking with bad prevention attitudes 3 people (13%) and good 20 people (87%), the level of knowledge was sufficient with bad prevention attitudes 6 people (9%) and good 59 people (91%), good knowledge levels with a bad attitude 10 people (10%) and 85 people (90%). There was no significant relationship between the level of knowledge and the attitude of prevention (p = 0.828). In conclusion, there is no relationship between the level of knowledge and the attitude of preventing HIV/AIDS among students of SMAN 1 Cianjur for the academic year 2020–2021. Abstrak. Pendahuluan: Human Iimmunodeficiency Virus (HIV) merupakan virus yang menyerang sel darah putih sehingga terjadi penurunan sistem imun. Menurut data World Health Organization (WHO) pada tahun 2019 dinyatakan 38 juta orang terinfeksi HIV di seluruh dunia. Menurut Dinas Kesehatan Jawa Barat tahun 2018, Kota Cianjur menempati peringkat ke-13 dari 27 kabupaten/kota dengan laporan 124 kasus. Penyebaran HIV banyak terjadi di kalangan remaja akibat rendahnya tingkat pengetahuan terhadap faktor risiko HIV. Kesalahpahaman pengetahuan HIV/AIDS akan menjadikan banyak remaja mengalami kebingungan dan cenderung terpengaruh terhadap informasi tidak benar. Hal tersebut dapat diperparah dengan tidak adanya fasilitas pendukung di tingkat pendidikan formal dan pengaruh teknologi informasi dari media tanpa filter. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan dengan sikap pencegahan terhadap HIV/AIDS pada siswa-siswi SMAN 1 Cianjur tahun ajaran 2020–2021. Jenis penelitian kuantitatif dengan metode observasional analitik dengan pendekatan cross sectional. Data diperoleh dari penyebaran kuesioner kepada siswa-siswi SMAN 1 Cianjur berjumlah 95 sampel. Analisis data menggunakan uji gamma. Pengolahan data dilakukan dengan aplikasi SPSS 2.0 dengan derajat signifikansi p<0,005. Hasil penelitian didapatkan tingkat pengetahuan kurang dengan sikap pencegahan buruk 3 orang (13%) dan baik 20 orang (87%), tingkat pengetahuan cukup dengan sikap pencegahan buruk 6 orang (9%) dan baik 59 orang (91%), tingkat pengetahuan baik dengan sikap buruk 10 orang (10%) dan baik 85 orang (90%). Tidak terdapat hubungan bermakna tingkat pengetahuan dengan sikap pencegahan (p=0,828). Simpulan, tidak terdapat hubungan tingkat pengetahuan dengan sikap pencegahan HIV/AIDS di kalangan siswa-siswi SMAN 1 Cianjur tahun ajaran 2020–2021.